Renormalized Solution of the Relativistic Boltzmann Equation in a Robertson-Walker Spacetime (African Journal for Industrial and Applied Mathematics, 2025)
In this paper, the proof of the global existence of a renormalized or equivalently mild solution of the relativistic Boltzmann equation in a Robertson-Wakerspace-time is given for an initial value problem with initial data only satisfying theconditions of finite mass, energy, inertia and entropy.